AL-ISLAM EDUCATION AND KEMUHAMMADIYAHAN ISLAM-BASED DEVELOPMENT FOR NURSING STUDENTS - Irvan Shaifullah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2021)
Social change in the global era poses various challenges in the field of Al Islam and Kemuhammadiyahan education, which requires the implementation of a new paradigm of AIK education. On that basis, it is necessary to develop a curriculum based on the character of Advanced Islam to reconstruct theological, philosophical, substantive aspects, methodology, and education system. This research method uses qualitative research type with Research and Development (R&D) approach used to produce a particular product, and tests the effectiveness of the method by data collection techniques in the form of obersevasi, interview and documentation. In the development of this curriculum it can be concluded that the integration between science and materials of Al Islam and Kemuhammadiyah in shaping the character of Advanced Islam at the PTM-A level is highly recommended by prioritizing the analysis of needs, product design, validation and evaluation for curriculum development in each PTM-A. Consistent implementation and evaluation strategies are the benchmarks for the success of the AIK curriculum based on this advanced Islamic character. The standard profile of character, learning achievements and competence is very decisive for the progress of Islam in the future. For a graduate of PTM-A, the standard character of Advanced Islam has a special characteristic that is beraqidah straight, integrity, innovative, professional, sincere, educational and communicative, able to cooperate and amar ma'ruf nahi munkar.